Management of diabetic ketoacidosis in pregnancy. (January 2017) - Mohan, Manoj; Baagar, Khaled Ahmed Mohamed; Lindow, Stephen
Abstract : Key content: Diabetic ketoacidosis in pregnancy (DKP) is a serious complication that poses several challenges with respect to diagnosis, management and prevention. This article covers the precipitating factors for DKP in pregnancy as well as diagnosis, management and prevention of the complication. Learning objectives: To manage the acute crisis of DKP. To increase awareness of DKP. To reduce the perinatal morbidity and mortality associated with DKP. Ethical issues: Despite adequate knowledge and care of patients with diabetes, is DKA a major cause for concern? To increase awareness, and reduce the perinatal morbidity and mortality associated with DKP.